Simulation of Teaching Activities in the Training of Bachelors in Psychological-Pedagogical Direction - Sokolov V.L. (Психолого-педагогические исследования)
The article presents the results of testing an innovative product, developed in MSUPE, simulation teaching activities of the mathematics teacher of the first class. Discusses the possibility of using simulation for the formation of the labour features of the future teachers. The analysis of the place of use of the simulator in the context of the modular principle of teacher education that combines learning of the theoretical knowledge with their practical application. Are obtained in the course of the study, data on changes in the ability to carry out meaningful reflection, reducing external learning motivation in the experimental group of students. On the basis of the observations given the qualitative analysis of students ' attitudes toward a new software product and its role in the development of the content of the training module. A number of conclusions about the effects and prospects of the use of simulation teaching.